A unified approach to design controller in cascade control structure for unstable, integrating and stable processes. (August 2021) - Siddiqui, Mohammad Atif; Anwar, M.N.; Laskar, S.H.; Mahboob, M.R.
Abstract: This article presents a unified approach of controller design in cascade control structure (CCS) for unstable, integrating and stable processes with dead-time to achieve enhanced load disturbance rejection. The design of inner and outer loop controllers in CCS is based, partially on the direct synthesis approach and partially on the pole placement method. First, the parameters of the inner loop controller are obtained and then the outer loop controller is designed by considering the inner loop as a part of the primary plant. The proposed design approach deals with a wide range of processes having unstable, integrating and stable dynamics in a unified way. It is applied directly on the higher and lower order processes, as the proposed strategy is acquitted from the approximation of the dead-time and model order reduction of the plant. Simulations have been conducted to show the efficacy of the present approach. The results shows that the present approach provides enhanced regulatory performance as compared to the recently reported approaches from the literature.